1993
DOI: 10.1128/mcb.13.7.4029
|View full text |Cite
|
Sign up to set email alerts
|

The yeast alpha 2 protein can repress transcription by RNA polymerases I and II but not III.

Abstract: The ca2 protein of the yeast Saccharomyces cerevisiae normally represses a set of cell-type-specific genes (the a-specific genes) that are transcribed by RNA polymerase II. In this study, we determined whether cv2 can affect transcription by other RNA polymerases. We find that af2 can repress transcription by RNA (22,23,58,66,92,99,107). A TFIIB homolog involved in RNA polymerase III transcription has also been identified (10, 21, 59). Apparently, there are several common components within the different RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Morse (1993) also showed that GAL4, a transcriptional activator of genes transcribed by RNA polymerase II, is able to disrupt nucleosomes that are positioned by MATo~2. In addition, Herschbach and Johnson (1993) found that MATa2 could repress transcription of RNA polymerase I-transcribed genes but not of genes that are transcribed by RNA polymerase III. Although these latter results were interpreted to reflect interactions between MATch2 (and associated proteins) and specific transcriptional subunits shared by RNA polymerases I and II but not III, they are also consistent with numerous examples of changes in chromatin structure associated with activation of polymerase I-and IItranscribed genes (Prior et al 1983;Conconi et al 1989;Wolffe 1992).…”
Section: Tup1mentioning
confidence: 99%
“…Morse (1993) also showed that GAL4, a transcriptional activator of genes transcribed by RNA polymerase II, is able to disrupt nucleosomes that are positioned by MATo~2. In addition, Herschbach and Johnson (1993) found that MATa2 could repress transcription of RNA polymerase I-transcribed genes but not of genes that are transcribed by RNA polymerase III. Although these latter results were interpreted to reflect interactions between MATch2 (and associated proteins) and specific transcriptional subunits shared by RNA polymerases I and II but not III, they are also consistent with numerous examples of changes in chromatin structure associated with activation of polymerase I-and IItranscribed genes (Prior et al 1983;Conconi et al 1989;Wolffe 1992).…”
Section: Tup1mentioning
confidence: 99%
“…In yeast, mating type silencing has been shown to affect both RNA polymerase II and III transcription (Brand ef a/., 1985;Schnell and Rine, 1986), while the corepressor complex TUP1/SSN6 is known to repress transcription by RNA polymerase I and II, but not that by RNA polymerase III (Herschbach and Johnson, 1993). Therefore, we chose the adenovirus VA RNA I gene to test whether the KRAB domain would affect RNA polymerase III driven transcription.…”
Section: Sp1/5gmentioning
confidence: 99%
“…We proposed that the role of Mata2p is to recruit the Ssn6p-Tuplp complex which in turn mediates repression of the AMTaspecific gene (24). Although several mechanisms for Mata2p-mediated AMTa-specific gene repression have been proposed (15,21,23,44,45,48), the molecular basis of this repression is not understood.The most striking structural feature of a repressed AL4Ta-specific gene in a AM Ta cell is the presence of a regular array of nucleosomes covering the promoter area and extending into the structural gene (48). The generation of this Mata2p-dependent nucleosome array adjacent to the Mata2p operator has been characterized in the TRPlARS1-derived multicopy TASTE and TALS plasmids (44), as well as in the single-copy genomic AMTa-specific STE6 and BAR1 genes (48).…”
mentioning
confidence: 99%
“…We proposed that the role of Mata2p is to recruit the Ssn6p-Tuplp complex which in turn mediates repression of the AMTaspecific gene (24). Although several mechanisms for Mata2p-mediated AMTa-specific gene repression have been proposed (15,21,23,44,45,48), the molecular basis of this repression is not understood.…”
mentioning
confidence: 99%